RUPIAH EXCHANGE RATE DETERMINANTS - Jason Tandani; Afrizal Nilwan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The rupiah exchange rate has continued to depreciate over the past few years. The weakening of the exchange rate can have an impact on transaction activities in Indonesian society and international trade. Several factors can be the cause of the weakening of the rupiah exchange rate against the United States dollar, such as domestic inflation, exports and imports. This study aims to determine the influence of inflation, exports and imports on the exchange rate of the Indonesian rupiah against the United States dollar during 2019-2023. This study uses a multiple linear regression analysis method with time series and cross section data types obtained from the website of the Ministry of Trade of the Republic of Indonesia. The results of this study are (1) inflation has a positive effect on the exchange rate; (2) exports have a positive effect on the exchange rate: (3) imports have a negative effect on the exchange rate.